Synthesis of Metal/Silica/Titania Composites for the Photocatalytic Removal of Methylene Blue Dye - Sana Ahmad; Arfa Saeed (Journal of Chemistry)
The present work deals with the synthesis of the metal-doped titanium dioxide/silica composite by using the sol-gel method. The structure, morphology, and composition of the prepared samples were characterized by using Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). The prepared composites were used for the photodegradation of methylene blue dye in sunlight. Different parameters like pH, time, and catalytic concentration were varied to optimize the reaction conditions. Maximum 99.8% degradation was observed with the Ni-doped composite. The results indicate extraordinary efficiency of all metal-doped composites for the removal of the harmful organic pollutant like methylene blue.